Effects of altered blood flow induced by the muscle pump on thrombosis in a microfluidic venous valve model. Issue 14 (16th June 2020) - Hu, Xiangyu; Li, Yongjian; Li, Jiang; Chen, Haosheng
Abstract : A microfluidic venous valve model to illustrate how the altered blood flow induced by the muscle pump influences venous thrombosis. Abstract : Deep vein thrombosis (DVT) often occurs in the lower limb veins of bedridden patients and greatly reduces the quality of life. The altered blood flow in venous valves induced by the insufficient efficacy of the muscle pump is commonly considered as a main factor. However, it is still a great challenge to observe the altered blood flow in real time, and its role in the formation of thrombi is poorly understood. Here we make a microfluidic venous valve model with flexible leaflets in a deformable channel that can mimic the motion of valves and the compression of vessels by muscle contraction, and identify the stasis and intermittent reflux in the valve pocket generated by the muscle pump. A thrombus forms in the stasis flow, while the intermittent reflux removes the fibrin and inhibits the growth of the thrombus. A flexible microfluidic device that can mimic the motion of valves and the contraction of vessels would have wide applications in the research on cardiovascular diseases.